Optimization of the Performance of Satintelkam in Preventing the Spread of Radical Beliefs in the Jurisdiction of Klaten Resort Police - Yudistira, Dhafi Kurnia (Advances in Police Science Research Journal, 2024)
Radical groups are groups that have ideological beliefs and fanatically struggle to change the current system of values and systems. The purpose of writing in this final project is to describe the Organizational Resources of Satintelkam and describe the performance of Satintelkam through investigations and efforts to prevent the spread of radicalism. The conceptual literature of this study uses Competency theory, Management theory, and SWOT analysis. While the concepts used include Intelligence concepts, Radical concepts, Optimization concepts, and Performance concepts. The writing method used is a qualitative method with descriptive writing and field writing. Sources of data include primary and secondary through interviews and documentation studies. Data validity was obtained using data triangulation. The writing location is Klaten Regency which is one of the areas of Central Java Province within the jurisdiction of the Klaten Police. Administratively, Klaten Regency is divided into 26 Districts, and is divided into 391 Villages and 10 Villages, 864 Hamlets which include 3,686 RWs, 9,607 RTs with a total of 480,764 Heads of Families. The findings during writing were (1) the Klaten Police Sanintelkam Organizational Resources did not fully support the activities and performance of Satintelkam such as a lack of personnel, limited budget, inadequate special intelligence tools, and understanding of applicable rules and (2) investigative and fundraising performance not optimal due to lack of awareness of personnel in terms of administration, ambiguityjob description personnel due to the absence of standard rules, the lack of ability to use investigative and fundraising tactics and techniques, and the weak supervision and control of data filing and intelligence products. The conclusions of the writing are (1) the utilization of organizational resources has not supported Satintelkam’s activities in preventing the spread of radical groups so that obstacles are found in its implementation and (2) the performance of early detection is not optimal according to applicable regulations so that problem solving is needed on the competence of knowledge, skills and attitudes of personnel Satintelkam.